Pola Asuh Otoriter Orang Tua terhadap Perkembangan Mental Anak - Erva Nurnawati (Gunung Djati Conference Series, 2023)
This study aims to discuss the authoritarian parenting style of parents on children's mental development. This research used a qualitative approach using descriptive analytical methods and this research was carried out through social media studies and literature studies. The formulation of the problem in this study is that there is an authoritarian parenting style for children's mental development. From the results of this study it can be concluded that parents really contribute fully in facilitating the process of children's mental development. Parents are people who help, supervise and guide their children so that they are mentally and physically healthy so that they do not deviate from various deviations from lack of trust and dependence on others. The role of parents is very helpful in complementing the mental development of children.